Analisis Terhadap Putusan Hakim Praperadilan di Pengadilan Negeri Medan - Sipayung, Jekson; Suhaidi, Suhaidi; Harianto, Dedi; Zulyadi, Rizkan (Universitas Medan Area, 2019)
The purpose of this study is to describe how the legal development of reasons for filing pretrial today, how the legal consequences of the fall of the judge's decision on the pretrial submission, and how criminal law policy formulates pretrial institutions in Indonesia's positive law in terms of human rights protection. This type of research uses normative juridical types. The results of research and discussion explain the development of the legal reasons for the submission of pretrial experiences development not only as stipulated in the Criminal Procedure Code but also in the Constitutional Court Decision No. 21 / PUU-XII / 2014 has expanded the pretrial object in the form of arrest, detention, cessation of investigation or termination of the prosecution as well as the stipulation of the determination suspect, search and seizure. The legal consequence of the fall of the judge's decision on the pretrial submission is that if the decision determines the arrest or detention is invalid, the investigator or public prosecutor must immediately release the suspect, in the event that the decision determines that a cessation of investigation or illegal prosecution, investigation or prosecution of the suspect must continue and in the case of a decision stipulating that an arrest or detention is not legal, then in the decision, the amount of compensation and rehabilitation given is stated, whereas in the case of cessation of an investigation or prosecution is valid and the suspect is not detained, the decision shall include the rehabilitation.